Increased prevalence of left ventricular hypertrophy in hypertensive women with type 2 diabetes mellitus - Adler Yehuda; Schwammenthal Ehud; Fisman Enrique Z; Tenenbaum Alexander; Benderly Michal; Motro Michael; Shemesh Joseph (Cardiovascular Diabetology, 2003)
Abstract Background Left ventricular hypertrophy (LVH) is a powerful independent risk factor for cardiovascular morbidity and mortality among hypertensive patients. Data regarding relationships between diabetes and LVH are controversial and inconclusive, whereas possible gender differences were not specifically investigated. The goal of this work was to investigate whether gender differences in left heart structure and mass are present in hypertensive patients with type 2 diabetes. Methods Five hundred fifty hypertensive patients with at least one additional cardiovascular risk factor (314 men and 246 women, age 52 to 81, mean 66 ± 6 years), were enrolled in the present analysis. In 200 (36%) of them – 108 men and 92 women – type 2 diabetes mellitus was found upon enrollment. End-diastolic measurements of interventricular septal thickness (IVS), LV internal diameter, and posterior wall thickness were performed employing two-dimensionally guided M-mode echocardiograms. LVH was diagnosed when LV mass index (LVMI) was >134 g/m2 in men and >110 g/m2 in women. Results Mean LVMI was significantly higher among diabetic vs. nondiabetic women (112.5 ± 29 vs. 105.6 ± 24, p = 0.03). In addition, diabetic women presented a significantly higher prevalence of increased IVS thickness, LVMI and left atrial diameter on intra-gender comparisons. The age adjusted relative risk for increased LVMI in diabetics vs. nondiabetics was 1.47 (95% CI: 1.0–2.2) in females and only 0.8 (0.5–1.3) in males. Conclusion Type 2 diabetes mellitus was associated with a significantly higher prevalence of LVH and left atrial enlargement in hypertensive women.